Juros sobre capital próprio: os aspectos que impactam o processo decisório das empresas na opção pelo pagamento da remuneração dos acionistas - Hoch, Valzeane Drehmer (Universidade do Vale do Rio dos Sinos, 2017)
This study seeks to identify the aspects that lead companies not to opt for Interest on Equity (JSCP), since there is a tax benefit for companies that choose to pay the compensation to their shareholders in this way. In order to do this, we test whether the size of the company, its profitability, its payout volume for the year, its level of corporate governance and the presence of legal entity in the controlling shareholder structure impact in the decision on the remuneration of its shareholders. In order to reach the proposed objective, we used the logit regression model in the companies listed on BM&FBovespa during the years 2009 to 2015. With an amount of 1,683 observations, we identified that: (i) companies with large assets (size), and those with no assets a legal entity in the controlling shareholder structureof the company is more likely to opt for remuneration to its shareholders in the form of JSCP; (ii) profitability, volume of payments in the year (payout) and commitment to good corporate governance practices do not seem to influence the decision to pay in the form of JSCP. In order to give greater robustness to the results found, with regard to the presence of legal entity, we segregate the sample between financial and non-financial companies. The segregation of the base is due to the differences in income tax and social contribution on net income between financial and non-financial companies. We found significance results for non-financial companies, while for financial companies, which have a higher tax base, there was no significance for the presence of legal entity. Such results reinforce the theory that principal-principal agency conflicts as well as taxes can be a major determinant of corporate shareholder decisions.
Keywords: Política de distribuição de lucros; Remuneração de acionistas; Juros Sobre Capital Próprio (JSCP); Dividendos; Tributação; Payout policy; Remuneration of shareholders; Interest on equity (JSCP); Dividends; Tax; ACCNPQ::Ciências Sociais Aplicadas::Ciências Contábeis